A hybrid differential evolution and harmony search for nonconvex economic dispatch problems - Le, Dinh Luong; Vo, Ngoc Dieu; Nguyen, Thanh Hop; Le, Anh Dung (2013 IEEE 7th International Power Engineering and Optimization Conference (PEOCO), 2013)
In this paper, we presents a novel approach for solving economic dispatch (ED) problems with nonconvex cost functions using a hybrid differential evolution and harmony search (DENS). The DENS method is an improved differential evolution method based on the harmony search scheme. The DENS method has the flexible adjustment of the parameters to get a better optimal solution. Moreover, an effective constraint handling framework in the method is employed for properly handling equality and inequality constraints of the problem. The proposed DENS has been tested on three systems with 40, 15 and 140 units and the obtained results from DENS algorithm have been compared to those from other methods in the literature. The result comparison has indicated that the proposed DENS method is more effective than many other methods for obtaining the optimal solution for the test systems. Therefore, the proposed DENS is a very favorable method for solving the nonconvex ED problems.